A comparison of open source geospatial technologies for web mapping. (1st January 2011) - Ballatore, Andrea; Tahir, Ali; McArdle, Gavin; Bertolotto, Michela
The past decade has witnessed a steady growth of open source software usage in industry and academia, leading to a complex ecosystem of projects. Web and subsequently geographical information systems have become prominent technologies, widely adopted in diverse domains. Within this context, we developed an open source web platform for interoperable GIServices. In order to implement this architecture, 14 projects were selected and analysed, including the client-side libraries and the server-side components. Although other surveys have been conducted in this area, little feedback has been formally obtained from the users and developers concerning their opinion of these tools. A questionnaire was designed to obtain responses from the relevant online communities about a given set of characteristics. This article describes the technologies and reports the results of the survey, providing first-hand information about open source web and geospatial tools.